2021
DOI: 10.1002/est2.263
|View full text |Cite
|
Sign up to set email alerts
|

Design, simulation and analysis of a fast charging station for electric vehicles

Abstract: With the advent of Electric Vehicles into existence, there is a need to develop a significantly charging infrastructure that will make electric cars more attractive and lead to higher adoption rates. In light of the increasing demand for EVs, there is a need to develop a fast‐charging station that cuts back on the charging time and hence overcome range anxiety. Fast charging stations are capable of reducing the charging duration by up to 30 min. By way of sustainable development and availability of secure ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The magnitude of the induced emf voltage in the pick-up Rx coil is proportional to the coupled flux and no. of turns in the coil, which is governed by faradays law equation (2).…”
Section: Wript Technology For In-motion Ev Charging Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the induced emf voltage in the pick-up Rx coil is proportional to the coupled flux and no. of turns in the coil, which is governed by faradays law equation (2).…”
Section: Wript Technology For In-motion Ev Charging Applicationmentioning
confidence: 99%
“…Charging duration of EV with respect to power capacity and range travel distance, addressed by fast charging system. Fast charging systems reduced the charging duration of the EV and raise power charging capacity, which will enhance the distance traveled (milage) by the EV [2]. EV charging system aids the advantage of the utilization of sustainable energy sources and is a promising approach to elevate society toward sustainability which addresses climate change actions [3].…”
mentioning
confidence: 99%
“…It should be borne in mind that, the actual use of such power, is highly dependent on the ability of the battery pack to accept such power by effectively managing the thermal issues and the state of health maintenance [25]. In any case, fast charging allows 80% of the battery capacity to be reached in tens of minutes [26]. Charging the remaining 20%, if conducted efficiently, would take longer [27].…”
Section: Fast-charging Infrastructurementioning
confidence: 99%
“…When there is no physical barrier between the charger and the battery, isolation monitoring is essential. A fast-charging station [6]- [7] proposed to charge an EV up to 80% SoC within 30 minutes of charging time. The CHAdeMO group recently unveiled a new charging methodology.…”
Section: Figure 1 Overall Structure Of Review Articlementioning
confidence: 99%
“…(5) ) ω r (6) The SAE suggested that the operating frequency of the DWC system is 85 kHz [28]. The skin effect and proximity effects are high in this HF range.…”
Section: A Charging Couplersmentioning
confidence: 99%